2003
DOI: 10.1046/j.1440-1797.8.s.2.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of dialysate sodium in sodium profiling haemodialysis

Abstract: Sodium profiling haemodialysis is a modified method of sodium gradient dialysis during which dialysate sodium follows a time-dependent profile. Sodium profiling haemodialysis has claimed to reduce intradialytic discomforts such as hypotension, muscle cramps, and disequilibrium syndrome. Having the low sodium period is an essential part of the sodium profiling haemodialysis to compensate for the sodium gain during the high sodium period. In spite of this, however, the incidence of interdialytic complications th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Because it is neutral with respect to the intradialytic diffusive sodium balance (7,8,16), it is theoretically possible that it avoids the sodium gain-associated complications while preserving hemodynamic tolerance. Despite the Figure 3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because it is neutral with respect to the intradialytic diffusive sodium balance (7,8,16), it is theoretically possible that it avoids the sodium gain-associated complications while preserving hemodynamic tolerance. Despite the Figure 3.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the negative consequences by sodium gain have been frequently reported: Thirst, excessive interdialytic weight gain, dyspnea, and the development of hypertension (8 -15). Independent of the detailed course of a profile, an important consideration during sodium profiling HD is the sodium balance that is determined by the intradialytic diffusive sodium transport: Positive, negative, or neutral (7,8,16). We recently reported that the time-averaged mean of dialysate sodium has a close relationship with the complication related to intradialytic diffusive sodium gain (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, and thanks to some strategies based on current practice, with particular reference to calcium and magnesium concentration in the dialysate [16,20], dialysate temperature [21] and ultrafiltration and sodium concentration profiles [7,22-25], pressure stability is guaranteed as a general rule. Some electrolytes, particularly sodium and bicarbonate, can be modulated in profiles with the purpose of better respecting the gap in osmolarity or concentration that is established during the haemodialysis session, but their haemodynamic effect still remains controversial [21,23,25]. …”
Section: Introductionmentioning
confidence: 99%
“…Despite this measure, the majority of sodium profiles result in a positive sodium balance as evidenced by increases in IDWG, thirst, and blood pressure (16). The time‐averaged dialysate sodium concentration during dialysis plays a key role in determining net sodium flux and whether positive sodium balance occurs (17,18). Thus, positive sodium balance in sodium profiles can result in a vicious cycle of increased interdialytic thirst, larger ensuing IDWG, the need for additional UF with dialysis, and consequent risk for IDH.…”
mentioning
confidence: 99%